3D Printing of Mechanically Resistant Poly (Glycerol Sebacate) (PGS)‐Zein Scaffolds for Potential Cardiac Tissue Engineering Applications. Issue 9 (30th March 2022) - Ruther, Florian; Roether, Judith A.; Boccaccini, Aldo R.
Abstract : Due to the limited regenerative capacity of the natural human myocardium, 3D printing of the cyclic polyester poly (glycerol sebacate) (PGS) offers a promising alternative to produce scaffolds (cardiac patches) for cardiac tissue engineering. Since the 3D printability and subsequent thermal crosslinking of pure PGS without any modification or additives are challenging, a PGS‐zein‐salt‐based printing process is developed in this work by mixing PGS pre‐polymer with ground and sieved sodium chloride particles and additionally with different amounts of the corn protein zein. The resulting inks show excellent printability and high shape fidelity both during the printing process and after thermal crosslinking. Chemical analysis indicates the successful integration of zein into the PGS backbone. Mechanical characterization shows the anisotropic behavior of the structure in the alternating printing direction. Subsequent biological assessments reveal no cytotoxic effects on C2C12 cells, rendering the developed PGS‐zein combination a suitable material for 3D printing of cardiac patches. Abstract : 3D printing of the cyclic polyester poly (glycerol sebacate) (PGS) offers a promising new approach to produce scaffolds for cardiac tissue engineering. A PGS‐zein‐salt‐based printing process is developed by mixing PGS pre‐polymer with sodium chloride particles and additionally with the corn protein zein. The resulting inks show excellent printability and high shape fidelity during printing and after thermal crosslinking.